HOME-BASED STRATEGIES FOR THE MANAGEMENT OF GINGIVITIS - Kurbanova, Aziza (ILMIY YANGILIKLAR VA INTELLEKTUAL TADQIQOTLAR, 2025)
Gingivitis, characterized by inflammation of the gingival tissues, is a prevalent oral health condition worldwide that, if untreated, may progress to periodontitis. Effective management at the early stage can prevent disease progression and preserve periodontal health. This review explores evidence-based home-care strategies for managing gingivitis, focusing on mechanical plaque control, chemical adjuncts, and traditional remedies. Emphasis is placed on proper toothbrushing techniques, interdental cleaning, the use of antimicrobial mouth rinses, and the role of herbal products. Clinical studies demonstrate that patient adherence to these home-based measures significantly improves gingival health and reduces inflammation. This article aims to provide dental practitioners and patients with practical guidelines supported by current research to optimize gingivitis management outside clinical settings.